2007
DOI: 10.1177/0040517507078743
|View full text |Cite
|
Sign up to set email alerts
|

Sound Absorption Coefficients of Micro-fiber Fabrics by Reverberation Room Method

Abstract: The sound absorption properties of materials are important not only for noise reduction, but also for controlling reverberation time for speech intelligibility in rooms and for promoting fuller sound in concert halls. Industrial textiles are focusing on these materials' application for sound absorption, thus new textiles were to be examined in relation to this performance. Micro-fiber fabric has fine fibers and a high surface area and it has been used in such applications as wipers, thermal insulator, filters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 5 publications
3
40
0
2
Order By: Relevance
“…The density of material exerts, however, a greater influence on sound absorption than the fabric thickness or weight [10]. In the case of composites, the values of sound absorption coefficients are small for low frequencies and usually they increase with increasing frequency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The density of material exerts, however, a greater influence on sound absorption than the fabric thickness or weight [10]. In the case of composites, the values of sound absorption coefficients are small for low frequencies and usually they increase with increasing frequency.…”
Section: Methodsmentioning
confidence: 99%
“…Nonwovens owing to their great surface area, especially those made on the basis of natural fibres or active carbon fibres, are often mentioned beside spacer knitted fabrics as fibrous materials with a relatively good acoustic behaviour [5][6][7][8][9][10][11][12] with respect to conventional materials such as foams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the rise in the thickness of absorbent materials leads to a decline in the number of peaks and causes some changes in the transmission loss peak frequency (14). Lancaster et al (2007) studied the impact of microfiber cloth on absorbing noise and concluded that the density of microfiber cloth plays a more important role than its thickness and weight in reducing noise (15). We found that silencers with higher density are better noise absorbents, a finding that is in line with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship between Cellulose Morphology and Beating Degree Figure 5 shows the effects of beating degree on the fines content, kink index, and crimp index. Compared with the raw pulp fibers, the kink index and crimp index decreased with increasing beating degree, as measured by the Schopper-Riegler method (Li and Xu 2011), from 14 °SR to 68 °SR, but the fines content increased as well (Attenborough 1971;Na et al 2007;Beg and Pickering 2008). As for the fines content test, measurements controlled by computer were based on the direction of polarized light.…”
Section: Foaming Process Analysismentioning
confidence: 99%